1991
DOI: 10.1210/mend-5-12-1845
|View full text |Cite
|
Sign up to set email alerts
|

Glycine 119 of Bovine Growth Hormone is Critical for Growth-Promoting Activity

Abstract: Bovine GH (bGH) analogs with single amino acid substitutions at positions 117 (bGH-E117L), 119 (bGH-G119R), and 122 (bGH-A122D) were generated. These analogs bind to mouse liver membrane preparations with affinities similar to native bGH. However, transgenic mice which express the analogs demonstrate different phenotypes ranging from dwarfism to gigantism. For example, expression of bGH or bGH-E117L result in large transgenic mice. In contrast, transgenic mice with a growth phenotype similar to nontransgenic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
128
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 163 publications
(132 citation statements)
references
References 45 publications
4
128
0
Order By: Relevance
“…This novel class of molecules consists of modified GH-core proteins, which harbor one steric mutation within binding site 2, namely the replacement of the helix ␣3 Gly with long and charged residues such as Lys or Arg. Initially introduced in the bovine hormone (G119R-bGH) (15), the Gly substitution in the human hormone was also shown to generate an antagonist (G120K/RhGH), and the crystal structure of the hGH⅐hGHR 2 complex revealed that the Arg/Lys could actually impede the formation of a functional receptor dimer (14). Subsequently, these studies have resulted in the approval of a GHR antagonist, Somavert (Pegvisomant for injection), as a drug for the treatment of acromegaly (16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This novel class of molecules consists of modified GH-core proteins, which harbor one steric mutation within binding site 2, namely the replacement of the helix ␣3 Gly with long and charged residues such as Lys or Arg. Initially introduced in the bovine hormone (G119R-bGH) (15), the Gly substitution in the human hormone was also shown to generate an antagonist (G120K/RhGH), and the crystal structure of the hGH⅐hGHR 2 complex revealed that the Arg/Lys could actually impede the formation of a functional receptor dimer (14). Subsequently, these studies have resulted in the approval of a GHR antagonist, Somavert (Pegvisomant for injection), as a drug for the treatment of acromegaly (16).…”
mentioning
confidence: 99%
“…PRL , it drags along the "lower part" of the hormone (regions [15][16][17][18][19][20][21][22][23][24][25][26][27][28] PRL and 125-136 PRL ). Region 15-28 PRL reaches its final position only when the second PRLR-ECD interacts at binding site 2.…”
mentioning
confidence: 99%
“…4). Mutational studies showed that replacing this Gly with several amino acids other than Ala resulted in an hGH antagonist (14). A subsequent report confirmed that replacing hGH G120 with arginine resulted in a GH antagonist (17).…”
Section: Gh As An Antagonist: the Role Of Gly-119 Substitutionmentioning
confidence: 93%
“…As with the triple-mutation analogue, all three of the single mutated analogues bound to the GHR with similar affinities. However, it was only when the G119 residue was substituted (bGH-G119R) that a dwarf transgenic mouse was produced (14). Thus functional antagonism of the GHR in the 3 D bGH analogue was determined by the amino acid in the G119R mutation.…”
Section: Structure -Function Relationship Of Ghmentioning
confidence: 99%
See 1 more Smart Citation